2020
DOI: 10.3892/etm.2020.9380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on hemodynamic changes and inflammatory responses in patients undergoing off‑pump coronary‑artery bypass grafting

Abstract: The aim of the present study was to determine the effect of dexmedetomidine on hemodynamic changes and inflammatory responses in patients undergoing off-pump coronary artery bypass grafting (OPCABG). A total of 300 patients about to receive OPCABG were randomized evenly into the control group (n=116) and study group (n=123). Intravenous dexmedetomidine pump infusion was administered to patients in the study group at a rate of 0.4 µg.kg-1 .h-1. The control group received physiological saline at the same infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We included 48 trials of 6273 participants (online Supporting Information, Figure S1 and Table S4) [11, 25–70]. Dexmedetomidine was compared with saline placebo in 26 trials, propofol in 10 trials and various other drugs in 12 trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 48 trials of 6273 participants (online Supporting Information, Figure S1 and Table S4) [11, 25–70]. Dexmedetomidine was compared with saline placebo in 26 trials, propofol in 10 trials and various other drugs in 12 trials.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity: I 2 = 92%, 2 = 51.7988, p < 0.01 Ammar [30] Azeem [31] Balkanay [32] Bulow [33] Chi [34] Cho [35] Corbett [36] Cui [37] Djaiani [38] Dong [71] Elgebaly [40] Elgebaly [39] Gao [74] Goksedef [41] Huang [44] Khalil [47] Khalil [46] Kim [48] Kim [73] Li [50] Likhvantsev [51] Liu [52] Maldonado [53] Massoumi [54] Mogahd [55] Momeni [56] Park [57] Shehabi [59] Shi [retracted] Shokri [60] Soh [63] Subramaniam [64] Tosun [65] Turan [11] Wu [66] Zhai [68] Zi [70] Total . Evaluations (GRADE) organisation [13], and assessed for interstudy heterogeneity using I 2 statistics, s-squared values and p values from the chi-squared test, as well as visually inspecting forest plots [14].…”
Section: Random Effects Modelmentioning
confidence: 99%
“…Hemodynamic stability was one of the secondary endpoints. Previous studies have suggested the beneficial effect of dexmedetomidine on hemodynamic stability [27,28] . Dexmedetomidine may induce biphasic hemodynamic alterations.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have suggested the beneficial effect of dexmedetomidine on hemodynamic stability. [ 27 , 28 ] Dexmedetomidine may induce biphasic hemodynamic alterations. Alpha-2 mediated vasoconstriction may result in transient tachycardia and elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients in the experimental group had vomiting reactions, while 6 patients in the control group had vomiting reactions. A study has also confirmed that DEX can reduce the stress response effectively, enhance immunity, and relieve postoperative pain and the incidence of adverse reactions in patients undergoing radical gastrectomy for gastric cancer [ 24 ]. This is consistent with the results of this work.…”
Section: Discussionmentioning
confidence: 99%